Dinamika Pengelolaan Filantropi Islam pada Komunitas Muslim Minoritas - Wahyuni, Sri; Ruslan, Ismail; Syahbudi (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This study aims to analyze the dynamics of Islamic philanthropy management within Muslim minority communities in Landak Regency, West Kalimantan, focusing on its practices, challenges, and development potentials in Ambarang and Tebedak Villages. Employing a qualitative approach, data were collected through observation, in-depth interviews, and documentation involving community leaders, religious figures, and Muslim residents actively engaged in zakat, infak, and sadaqah activities. The data were analyzed interactively through the stages of reduction, presentation, and conclusion drawing. The findings reveal distinct characteristics in philanthropic management between the two villages. Tebedak Village demonstrates a more transparent and participatory management system supported by an institutional structure that ensures planned and accountable implementation of philanthropic activities. In contrast, Ambarang Village is characterized by strong social capital, particularly solidarity and mutual cooperation, yet lacks formal governance mechanisms. Both villages illustrate that Islamic philanthropy serves not only as a means of social assistance but also as an instrument for economic empowerment, interfaith harmony, and social cohesion within minority settings. These findings highlight the importance of strengthening community based institutions and Islamic philanthropy education to sustain social development programs in minority Muslim areas